2005
DOI: 10.1089/vbz.2005.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Factors Associated with Bank Voles (Clethrionomys glareolus) and Concomitant Hantavirus in Northern Sweden

Abstract: Puumala virus (PUUV), genus hantavirus, causes nephropathia epidemica, a mild form of hemorrhagic fever with renal syndrome in humans. In this study, bank voles, the natural reservoir of PUUV, were captured at locations of previous human PUUV exposure and paired controls within a region of high incidence in northern Sweden. The aim of the study was to evaluate the influence of environmental factors on the abundance of bank voles and the occurrence of PUUV. The total number of voles and the number of PUUV-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 31 publications
4
57
0
Order By: Relevance
“…1). These results regarding the importance of old forest are in line with similar findings by Olsson et al (2005) and Voutilainen et al (2012). In contrast to both of these studies, we also studied the distribution of infected voles at the landscape scale and also the occurrence on mires on the habitat scale, which represent an important habitat in our study area and boreal areas in general (Ahti et al 1968) and to our knowledge has never been studied previously with respect to PUUV distribution.…”
Section: Spatial Variation Of Puuv Antibody Positive Bank Volessupporting
confidence: 88%
See 4 more Smart Citations
“…1). These results regarding the importance of old forest are in line with similar findings by Olsson et al (2005) and Voutilainen et al (2012). In contrast to both of these studies, we also studied the distribution of infected voles at the landscape scale and also the occurrence on mires on the habitat scale, which represent an important habitat in our study area and boreal areas in general (Ahti et al 1968) and to our knowledge has never been studied previously with respect to PUUV distribution.…”
Section: Spatial Variation Of Puuv Antibody Positive Bank Volessupporting
confidence: 88%
“…As old, often spruce-dominated forest is the main habitat of bank voles (Hansson 1978, Olsson et al 2005, the negative effect of forestry on the occurrence of PUUV antibody positive voles in spring has likely resulted from clear cutting and converting such forest into cut-over forest. As reported by Stenbacka et al (2010), young, thinned forests lack many forest structures commonly found in old forest, such as coarse downed logs, implying a decrease in shelter against predators and increasing predation risk.…”
Section: Spatial Variation Of Puuv Antibody Positive Bank Volesmentioning
confidence: 99%
See 3 more Smart Citations